Comparing a series of 8-quinolinolato complexes of aluminium, titanium and zinc as initiators for the ring-opening polymerization of rac-lactide. - Bakewell,C; Fateh-Iravani,G; Beh,D; Myers,D; Tabthong,S; Hormnirun,P; White,AJ; Long,N; Williams,CK (Dalton Transactions, 2015)
The preparation and characterization of a series of 8-hydroxyquinoline ligands and their complexes with Ti(iv), Al(iii) and Zn(ii) centres is presented. The complexes are characterized using NMR spectroscopy, elemental analysis and, in some cases, by single crystal X-ray diffraction experiments. The complexes are compared as initiators for the ring-opening polymerization of racemic-lactide; all the complexes show moderate/good rates and high levels of polymerization control. In the case of the titanium or aluminium complexes, moderate iso-selectivity is observed (Pi = 0.75), whereas in the case of the zinc complexes, moderate hetero-selectivity is observed (Ps = 0.70).